PENGARUH KUALITAS AKTIVA PRODUKTIF DAN PROFITABILITAS TERHADAP KINERJA KEUANGAN BANK YANG GO PUBLIC DI INDONESIA TAHUN 2005-2009 - Nastuti, Ganjar Putri (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2010)
In this research, the researches take a hypothesize that estimated the quality productive assets and profitability influence of performance finance of private public bank in Indonesia. Instrument of analysis that is used statistical testing approach is significance test, decision to accept and to reject Ho is made with basic statistical value (ttest and Ftest) is got from counting result then compared with table value to certain free degree. The result of analysis is used conducted independent variabel by together that ROA having the result more significant of finance bank. It means that can show profitability or significantly, it is KAP equal to 0,0247 dan ROA 0,000. And can show with F-test, where Fstatistic > Fhitung equal to 19,97695 > 3,07.